Pengaruh Pengetahuan Pajak Dan Sanksi Pajak Peraturan Pemerintah Nomor 23 Tahun 2018 Terhadap Kepatuhan Wajib Pajak UMKM Di Pusat Pasar Medan - Harisman, Jasri; Harmain, Hendra; Atika, Atika (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the effect of tax knowledge and tax sanctions on MSME taxpayer compliance at the Medan Market Center. Tax is participation in paying an amount of money owed to a country by the public and private individuals or maybe a business entity where the collection can legally be carried out by force, by not receiving direct benefits and being used to finance the needs of a country for the prosperity of society and people. Quantitative method with an associative approach, data collection techniques using a questionnaire the number of samples in this study were 100 people in the city of Medan. Sampling technique using a questionnaire. Data were analyzed by multiple linear regression method. The results of this study indicate that tax knowledge has a significant positive effect on MSME taxpayer compliance at Medan Market Center, tax sanctions have no significant effect on MSME taxpayer compliance at Medan Market Center.